The effect of eicosapentaenoic and docosahexaenoic acids on plasma lipid and lipoprotein metabolism in black patients with essential hypertension - Tichelaar, Hendrik Yme (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.